Investigating Excess Cash, Firm Value and Stock Liquidity Risk in Firms with Growth Opportunities or Financial Constraints - Mohammad Osoolian (University of Tehran, 2021)
Objective: Stock liquidity is one of the most critical factors for investors in the capital markets and one of the main functions of the stock exchange. The tendency to investigate this issue stems from the fact that investors decide to trade in the capital market by comparing the risk and return of investment opportunities, and liquidity risk is one of the main risks. Managers are considered this issue, and various aspects of it have been studied so far. The purpose of this study is to determine the effect of excess cash on firm value and investigating the benefits of cash holding in firms with higher growth opportunities or financial constraints. Methods: Liu's 2006 measure for liquidity risk is used, which instead of focusing on a specific aspect of liquidity risk, such as trading volume and the difference between the buy and sale price, covers all aspects of it. The present study is in the category of post-event research. The data used in the research is related to 189 firms of the Tehran Stock Exchange from 2008 to 2018. In this study, Jark-Bra, Arch-Engel, BDS, Box-Pierce, IPS unit root, cohesion test, F-Limer, Hausman tests were used to evaluate descriptive statistics and results. Results: Excess cash has recently been considered by researchers as one of the measures for estimating the liquidity risk of firms. The research variables were examined for reliability. For this purpose, IPS test were used. Based on the results of this test, all research variables except for the cost of Research and Development (R&D) which is scaled by sales and institutional shareholders are at a stable level, while the latter variables are stable with a one-time differentiation. Accordingly, due to the lack of significance of a number of variables in the level, the existence of a long-run relationship was tested by the co-integration test method. The results of the test show that despite the unreliability of some research variables at the level, there is a long-term relationship between research variables. The results indicate that excess cash is a valuable criterion for firms’ liquidity risk and its effect becomes more severe under the influence of growth opportunities or financial constraints. Conclusion: The results indicate that the excess cash had a significant negative effect on the value of the firms. Additionally, in the study of firms with growth opportunities or financial constraints, it is found that for firms that have growth opportunities or financial constraints, the relationship between excess cash and liquidity of firms’ shares was more intense.